2012
DOI: 10.1007/s10661-012-2558-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in heavy metal contamination in water and sediments of river Sabarmati and Kharicut canal at Ahmedabad, Gujarat

Abstract: The objective of the study is to reveal the seasonal variations in the river water and sediment quality with respect to heavy metal contamination. To get the extent of trace metals contamination, water and sediment samples were collected from five different sites along the course of Sabarmati River and its tributary Kharicut canal in pre-monsoon, monsoon and post-monsoon seasons. The concentration of trace metals such as chromium, copper, lead, nickel and zinc was determined using inductively coupled plasma sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 12 publications
7
34
0
1
Order By: Relevance
“…The metal concentrations in the Taipu River were 1.1–3.0 times higher in the early rainy season than in the dry season, with the Cu, Mn, and Zn concentrations being more than two times higher in the early rainy season than in the dry season.The average metal concentrations in the Wusong River were 1.7–5.2 times higher in the early rainy season than in the dry season, with the Cr, Cu, Fe, Pb, V, and Zn concentrations being more than two times higher in the early rainy season than in the dry season. These temporal variations in the metal concentrations were generally consistent with seasonal variations in metal concentrations that have been found in other rivers [6,7]. …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The metal concentrations in the Taipu River were 1.1–3.0 times higher in the early rainy season than in the dry season, with the Cu, Mn, and Zn concentrations being more than two times higher in the early rainy season than in the dry season.The average metal concentrations in the Wusong River were 1.7–5.2 times higher in the early rainy season than in the dry season, with the Cr, Cu, Fe, Pb, V, and Zn concentrations being more than two times higher in the early rainy season than in the dry season. These temporal variations in the metal concentrations were generally consistent with seasonal variations in metal concentrations that have been found in other rivers [6,7]. …”
Section: Resultssupporting
confidence: 87%
“…The contributions of these sources are different in different regions and in different seasons, so heavy metal concentrations in surface water can vary both spatially and seasonally. Information on these variations is important for decision makers involved in environmental risk management [5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…As such, the lower concentrations of heavy metals during the monsoon may be due to the dilution effect of pollutant [35,36]. These temporal variations in the metal concentrations were generally consistent with seasonal variations in metal concentrations that have been reported in other rivers [37,38,39]. The possible reasons for higher concentration of metals at Site-2 followed by Site-3 might be due to presence of large drains at those sites that regularly empty their contents without treatment into the river.…”
Section: Results and Discussion Distribution Of Metals In Different Ssupporting
confidence: 81%
“…According to Kıvrak and Gürbüz (2010) Heavy metals are widespread pollutants of great environmental concern as they are non-degradable, toxic and persistent with serious ecological ramifications on aquatic ecology (Aboud and Nandini 2009). Industrial and agricultural activities often results in introduction of nutrients and potentially hazardous levels of heavy metal into the river ecosystem (Kumar et al 2013). But during this study, whereas the lowest Iron level in the Tortum Stream was found as 0.01±0.00 mgL -1 at S1, S2, S5, S8 (T2) and S9 (T3) was found as 1.08±0.01 mgL -1 at S4 where the discharge of agricultural effluent is the point source of pollution (Table 2).…”
Section: Discussionmentioning
confidence: 99%